Protein kinase C and NF-κB-dependent CD4 downregulation in macrophages induced by T cell-derived soluble factors: consequences for HIV-1 infection. - Raposo, R; Trudgian, D; Thomas, B; Van Wilgenburg, B; Cowley, S; James, W (American Association of Immunologists, 2011)
Upon activation, CD4(+) T cells release cytokines, chemokines, and other soluble factors that influence the kinetics of HIV-1 replication in macrophages (M). In this article, we show that activation of human primary T cells suppresses the early stages of HIV-1 replication in human primary Mφ by downregulating the main cellular receptor for the virus CD4. The secreted factors responsible for this effect have a molecular mass greater than conventional cytokines, are independent of Th1 or Th2 polarization, and are not IFN-γ, IL-16, RANTES, or macrophage inhibitory factor, as revealed by cytokine array analysis and neutralization assays. CD4 downregulation is entirely posttranslational and involves serine phosphorylation of CD4 and its targeting to an intracellular compartment destined for acidification and degradation. CD4 downregulation is dependent on the activities of both protein kinase C and NF-κB as well as the proteasomes. Using high-resolution liquid chromatography-tandem mass spectrometry analysis in conjugation with label-free protein quantitation software, we found that proteins that promote Mφ adherence and spreading, such as attractin, fibronectin, and galectin-3-binding protein, were significantly overrepresented in the activated T cell supernatant fractions. These results reveal the existence of previously unreported anti-HIV-1 proteins, released by activated T cells that downregulate CD4 expression, and are of fundamental importance to understand the kinetics of HIV infection in vivo.